2012
DOI: 10.4236/pp.2012.34052
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Angiotensin II on Intra-Renal Hemodynamics in Rats; Contribution of Prostanoids, NO and K<sup>+</sup> Channels

Abstract: Many agents are known to cause qualitative and quantitative differences in intrarenal blood flow. This study tested the hypothesis that angiotensin II (AII) evokes a differential effect on cortical (CBF) and medullary blood flow (MBF) and that AT<sub>2</sub> receptor mediates AII-induced increase in renal MBF by mechanisms related to nitric oxide (NO) and prostanoids. AII (100, 300 and 1000 ng/kg/min) increased mean arterial blood pressure (MABP) by 24% ± 7% (p < 0.05); decreased CBF by 30% ± 2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Changes in renal CBF are not always replicated in the medullary or papillary regions because medullary hemodynamics can be regulated independently of renal CBF (Pallone et al 1990, Navar et al 1996, Mattson 2003. Vasoactive agents, including AngII, dopamine, arginine vasopressin, atrial natriuretic peptide, and bradykinin have been demonstrated to induce renal region-specific hemodynamic changes (Takezawa et al 1987, Pallone et al 1990, Nobes et al 1991, Mattson & Cowley 1993, Heyman et al 1995, Badzynska et al 2002, Igbe et al 2012. However, the effect of UII on regional RBF was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in renal CBF are not always replicated in the medullary or papillary regions because medullary hemodynamics can be regulated independently of renal CBF (Pallone et al 1990, Navar et al 1996, Mattson 2003. Vasoactive agents, including AngII, dopamine, arginine vasopressin, atrial natriuretic peptide, and bradykinin have been demonstrated to induce renal region-specific hemodynamic changes (Takezawa et al 1987, Pallone et al 1990, Nobes et al 1991, Mattson & Cowley 1993, Heyman et al 1995, Badzynska et al 2002, Igbe et al 2012. However, the effect of UII on regional RBF was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The animal was allowed a 45-minute equilibration before the commencement of drug administrations. Blood pressure returned to baseline in-between drug administrations (Igbe et al 2012). The drugs were administered as follows: fumarate (0.1, 0.3, and 1 µg/kg), sodium nitroprusside (10, 30, and 100 µg/ kg) or PMA (1, 3, and 10 µg/kg).…”
Section: Acute Blood Pressure Studies In Normotensive Ratsmentioning
confidence: 99%